I dödens position? Ekonomisering och professionalisering inom travsporten - Berglund, Sara (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2002)
There is a crisis in Swedish harness racing! This is a widely held opinion by trainers and horse owners in the business. Economic expectations are no longer fulfilled by the actual development; training business go bankrupt, and the gamblers desert the racing arenas. Today, harness racing is not only a sport but also a gambling market, which leaves its marks on the economy, the ideology and the everyday life of trainers, owners and horses. The aim of this article is to discuss some of the processes that have given the business its current shape, focusing especially of professionalization.